2020
DOI: 10.1371/journal.pone.0232516
|View full text |Cite
|
Sign up to set email alerts
|

Regional citrate anticoagulation versus no-anticoagulation for continuous venovenous hemofiltration in patients with liver failure and increased bleeding risk: A retrospective case-control study

Abstract: Objective There are controversial opinions on anticoagulation for continuous venovenous hemofiltration (CVVH) in patients with liver failure (LF) and increased bleeding risk. Therefore, we conducted a retrospective study to evaluate the efficacy and safety of regional citrate anticoagulation (RCA) versus no-anticoagulation for CVVH in these patients. Methods The included patients were divided into RCA and no-anticoagulation group according to the CVVH anticoagulation strategy they accepted for CVVH. Filter lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…This study reported a higher Ca tot /Ca 2+ ratio (> 2.5) and two ACLF patients (28.5%) showed evidence of citrate accumulation during citrate infusion. Although, many studies have performed CRRT using RCA and reported a low incidence of citrate accumulation via intensive monitoring of the calcium and acid–base status 17 , 28 30 , our study showed the potential for citrate accumulation in patients with liver impairment.…”
Section: Discussionmentioning
confidence: 56%
“…This study reported a higher Ca tot /Ca 2+ ratio (> 2.5) and two ACLF patients (28.5%) showed evidence of citrate accumulation during citrate infusion. Although, many studies have performed CRRT using RCA and reported a low incidence of citrate accumulation via intensive monitoring of the calcium and acid–base status 17 , 28 30 , our study showed the potential for citrate accumulation in patients with liver impairment.…”
Section: Discussionmentioning
confidence: 56%
“…Clinicians may choose not to use pharmacologic anticoagulation in patients at high risk of bleeding, but the risk of circuit clotting and interruption of treatment is higher. In a cohort of 103 patients with liver failure on CRRT, filter life was significantly longer in the RCA group versus the no-anticoagulation group (>72 versus 39.5 h) (48). However, bleeding incidence was similar in both groups (5.1% in the RCA group versus 4.3% in the noanticoagulation group), suggesting that RCA use is a safe option in patients with a higher risk of bleeding.…”
Section: Anticoagulationmentioning
confidence: 93%
“…2,22,23 Reassuringly, a recent case-control study of patients with liver failure receiving CRRT demonstrated longer filter life, fewer filter failures, and no increased bleeding or metabolic complications in those receiving citrate anticoagulation compared with those without anticoagulation. 24 Furthermore, a recent SRMA by Zhang et al 25 addressed this same question. They included 10 studies with 1241 patients with liver dysfunction requiring CRRT.…”
Section: Deciding To Anticoagulatementioning
confidence: 97%
“…Anticoagulation is often deferred for these patients due to the risk of bleeding complications and/or the risk of hypocalcemia and metabolic acidosis related to the inability of the liver to metabolize citrate 2,22,23. Reassuringly, a recent case-control study of patients with liver failure receiving CRRT demonstrated longer filter life, fewer filter failures, and no increased bleeding or metabolic complications in those receiving citrate anticoagulation compared with those without anticoagulation 24. Furthermore, a recent SRMA by Zhang et al25 addressed this same question.…”
Section: Deciding To Anticoagulatementioning
confidence: 99%